X-ray powder diffraction of mineral pigments and medicines from the 17th century pharmacy (Spezieria) Santa Maria della Scala in Rome, Italy. Issue 4 (25th October 2018) - Cavallo, Giovanni; Vázquez de Ágredos Pascual, Maria Luisa
Abstract : The pharmacy ( spezieria ) Santa Maria della Scala was founded in Rome by the Discalced Carmelites Order in the 17 th century, and during the 18 th and 19 th centuries it became the official supplier of medicines for Vatican Popes. The laboratory and the cases of this spezieria still preserve glass jars with organic and inorganic materials, which were presumably used for medicine and artistic material preparation, whose composition is unknown to date. A research project was initiated with the aim to study the stored materials and the role that the pharmacy played in regional, national and international contexts. In this manuscript, the compounds were analysed through X-ray powder diffraction with the scope to derive the quantitative mineralogical composition of the inorganic fraction, their possible use in pharmacopoeias and as mineral pigments. Most of the analysed samples are salts (sulphates, chlorides, carbonates, phosphates, borates, sulphides), sulphates being the predominant class; oxides were also detected.